Morphology and leukocyte values in the experimental chagas disease - de Bonilla, Leonor; Diez Ewald, María; Negrette, Américo (Investigación Clínica, 2013)
Morphological alterations of leukocytes were studied in three groups of mice: one injected intraperitoneally with trypanosome infected blood, another that was injected with normal blood, and a third group that was injected with normal saline solution. On the 5th day after inoculation, leukopenia was observed in the infected mice and leukocytosis in those that received normal blood, in comparison with the group that only received saline. Both findings were more accentuated on the 10th day; but on the 15th day the leukocyte counts reached normal values in the infected group, remaining high in the blood injected one. The differential formula showed lymphocytosis and neutropenia in the two groups injected with blood, but a high increase of leukocyte debris was only observed in the infected group. This finding coincided with the lower neutrophil levels and the time of maximum parasitemia. The presence of the parasite in peripheral blood may be correlated with an increase of cellular Iysis. In fact, an increase of leukocyte debris was observed when the parasitemia and leukopenia were greater.